Condyloma Acuminata In Female Young Adult: A Case Report - Luvea, Luvea; Masita, Ritami (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
Condyloma acuminata (CA) is caused by human papillomavirus (HPV), predominantly low-risk types 6 and 11, which account for 90% of genital warts. The World Health Organization (WHO) 2023 estimates that 1% of sexually active adults worldwide have clinical CA, with higher rates among young adults aged 20–29. Factors like early sexual activity, multiple sexual partners, and unprotected sex increase susceptibility. Immunocompromised individuals are more likely to have persistent infections. A 2021 study in Jakarta found that 78% of CA patients delayed seeking care due to shame, with women and LGBTQ+ individuals most affected. This case underscores the complexity of managing condyloma acuminata, particularly in young, sexually active individuals. We presented a 22-year-old woman with a history of sexual relations with a lover whose history of sexually transmitted infections is unknown and not using protection such as condom. Comes with complaints of warts on the genitals since the last week. Complaints are accompanied by itching and pain around the genital warts. Venereology status reported lesions were found in the form of multiple verrucous papules with a base of erythematous macules that were clearly demarcated on the vaginal vestibule et frenulum labialis et clitoris of the vagina, with a localized distribution and miliary to lenticular size. An HIV serology examination was carried out and the result was non-reactive. Acetowhite test positive. The lesions are given drops of 90% trichloroacetic acid (TCA).